2018
DOI: 10.1002/ese3.259
|View full text |Cite
|
Sign up to set email alerts
|

Study on the mechanisms of refracturing technology featuring temporary plug for fracturing fluid diversion in tight sandstone reservoirs

Abstract: Well production rates in unconventional plays usually decline dramatically in the first year. Refracturing, which is a remedial production operation, is often done because original hydraulic fracturing failed to contribute any significant amount of flow or significant unfractured pay exists in the well. In order to maximize the fracturing fluid contact with the intact rock and to stimulate more reservoir volume in previously stimulated wells, a refracturing technology featuring a novel temporary plugging for f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Then, the chase gel breaker is injected to react with the polymer gel, and it will de finally degraded it into a lowviscosity liquid, reducing damage to the reservoir (Wang et al 2019a). The fiber-type TPA realizes the plugging effect mainly through the three processes of capturing, bridging, and compacting (Li et al 2019). After plugging treatments, the fiber-type TPA can be completely dissolved in water or residual acid, which can protect the reservoir from damage.…”
Section: Edited By Yan-hua Sunmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the chase gel breaker is injected to react with the polymer gel, and it will de finally degraded it into a lowviscosity liquid, reducing damage to the reservoir (Wang et al 2019a). The fiber-type TPA realizes the plugging effect mainly through the three processes of capturing, bridging, and compacting (Li et al 2019). After plugging treatments, the fiber-type TPA can be completely dissolved in water or residual acid, which can protect the reservoir from damage.…”
Section: Edited By Yan-hua Sunmentioning
confidence: 99%
“…In recent years, temporary plugging technology has been widely used in various fields of petroleum reservoir drilling and production (Kang et al 2014;Xiong et al 2018;Zhang et al 2019a). The design idea of temporary plugging technology is to use plugging agents (usually chemical agents) to plug the flow channels (i.e., layers with higher permeability) (Li et al 2019;Liu et al 2018). However, in the subsequent oil and gas production process, it is hoped that the agents sealing in the layers can be effectively removed or self-recovered (Zhang et al 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Refracture can be created in two forms: one form is that the directions of the new fracture propagate the same as the original fracture, and the other is that the directions of the new fracture propagate to a new direction with the redistribution of pressure. The conventional theory of hydraulic fracturing is built on tensile failure of rocks [10][11][12]. Many studies have been carried out that the formation of fractures is mainly affected by induced stress, geological conditions, and production conditions.…”
Section: Introductionmentioning
confidence: 99%
“…With the depletion of traditional fossil energy sources, the technique of hydraulic fracturing is commonly used for enhancing oil, gas, and geothermal reservoir productivity. [1][2][3][4][5][6] The report on the World and China Energy Prospects 2050 (2017 Edition) points out that consumption of natural gas will be maintained at an average annual growth rate of 1.3% and oil will be increased by 0.3% a year until 2050. Meanwhile, it has been confirmed that the injection of fluids into the formation, especially hydraulic fracturing, is closely related to seismic activity.…”
Section: Introductionmentioning
confidence: 99%